Design of a novel EmTSP-3 and EmTIP based multi-epitope vaccine against Echinococcus multilocularis infection - Fan, Yichen; He, Yueyue; Li, Yujiao; Yin, Zhengwei; Shi, Juan; Tian, Tingting; Shang, Kaiyu; Shi, Huidong; Zhang, Fengbo; Wen, Hao (Frontiers in Immunology, 2024)
Background: Current treatments and prevention strategies for echinococcosis are inadequate. Recent advancements in molecular vaccine development show promise against Echinococcus granulosus; however, Echinococcus multilocularis remains a challenge. A Multi-epitope Vaccine could potentially induce specific B and T lymphocyte responses, thereby offering protection against Echinococcus multilocularis infection. Methods: This study aimed to develop a MEV against alveolar echinococcosis. Key epitopes from the Echinococcus multilocularis proteins EmTSP3 and EmTIP were identified using immunoinformatics analyses. These analyses were conducted to assess the MEV feasibility, structural characteristics, molecular docking, molecular dynamics simulations, and immune simulations. The immunogenicity and antigenicity of the vaccine were evaluated through in vitro and in vivo experiments, employing ELISA, Western blotting, FCM, challenge infection experiments, and ELISPOT. Results: The effective antigenicity and immunogenicity of MEV were demonstrated through immunoinformatics, as well as in vitro and in vivo experiments. In vitro experiments revealed that MEV increased the secretion of IFN-γ and IL-4 in PBMC and successfully bound to specific antibodies in patient serum. Furthermore, mice immunized with MEV developed a robust immune response, characterized by elevated levels of CD4+ and CD8+ T-cells, increased secretion of IFN-γ and IL-4 by specific Th1 and Th2 cells, and heightened serum antibody levels. Importantly, MEV conferred protection against Echinococcus multilocularis infection in mice by reducing cyst weight. These findings suggest that MEV is a promising candidate for the prevention of Echinococcus multilocularis infection. Conclusions: A total of 7 CTL, 7 HTL, 5 linear B-cell, and 2 conformational B-cell epitopes were identified. The vaccine has demonstrated effective antigenicity and immunogenicity against AE through molecular docking, immune simulation, molecular dynamics studies, and both in vitro and in vivo experiments. It provides effective protection against Echinococcus multilocularis infection, thereby laying a foundation for further development.